Mycobacterium bovis infected domestic cats in an officially bovine tuberculosis free country resulting in human infection - Susanna Commandeur; Marleen van der Most; Jeroen Koomen; Lucien van Keulen; Annemieke Dinkla; Xander Luinenburg; Marieke Escher; Pieter Jacobs; Ingrid Keur; Guy C.M. Grinwis; Erik Weerts; Els M. Broens; et al. (One Health)
Although the Netherlands is an officially bovine tuberculosis (bTB) free (OTF) country, sporadic infections with Mycobacterium bovis still cause tuberculosis (TB) in (non-bovine) mammals, including humans. We describe for the first time cases of M. bovis infection in domestic cats in the Netherlands with transmission between companion animals and humans.In January 2023, a domestic cat, euthanized due to severe respiratory clinical signs, was diagnosed with M. bovis. Subsequently, three other cats from the household were euthanized and also diagnosed with M. bovis. The remaining kitten and dog received antibiotic treatment. Human contacts were screened using Tuberculin Skin Test (TST) and Interferon-Gamma Release Assay (IGRA). Lung lesions were detected in a TST+/IGRA− contact which tested positive for M. bovis DNA. This human lung-derived M. bovis DNA contained single nucleotide polymorphisms (SNPs) that were also identified in the DNA of M. bovis isolated from the cats in this household, strengthening the hypothesis of intra-species M. bovis transmission within the household. The four TST+ human contacts received antibiotic treatment. In the same period, another domestic cat from an unrelated household was euthanized due to respiratory clinical signs and diagnosed with M. bovis. This M. bovis strain differed 500 SNPs from the strains of the first household and was therefore genetically distinct. Commercially available, ready-to-use raw pet food was a suspected source in both households, however this could not be confirmed.These cases illustrate the need for one-health vigilance among both veterinarians and human physicians as essential to control outbreaks and prevent further spread to humans, companion animals, wildlife and livestock.